Pengaruh Mobile Game Bergenre Multiplayer Online Battle Arena (MOBA) terhadap Atensi Gamers - Vinanda, Ailsa Nabila Putri; Miranda, Aurelia; Diva, Dinda Aina Salsabila; Ahmadi, Diva Amara Nagea; Kemalleka, Marco; Lestari, Laila Indra (Flourishing Journal, 2024)
Attention is a fundamental cognitive process in the function of human anatomy, namely the brain. The mobile game industry continues to evolve both in terms of users and product variants. The activity of playing mobile games in the Multiplayer Online Battle Arena (MOBA) genre, such as Mobile Legends, is considered to require players to pay more attention when playing, for example in developing effective strategies to win the game. This study aims to determine the differences in attention between gamers and non-gamers. This study uses an experimental method with a between-subject research design and involves 60 participants consisting of 30 MOBA gamers as the control group and 30 non-gamers MOBA as the experimental group. The participants' attention was measured using an attention level measuring tool in the CogLab application version 2.0. The results of the study conducted through the independent samples t-test showed that there was a significant difference in attention between gamers and non-gamers with a significance value of p = 0.039. so the conclusion is that the level of attention in gamer participants as the control group showed higher results than non-gamer participants as the experimental group. AbstrakAtensi merupakan proses kognitif fundamental pada fungsi anatomi manusia, yaitu otak. Industri mobile game terus berevolusi baik dari sisi pengguna maupun varian produknya. Aktivitas bermain mobile game bergenre Multiplayer Online Battle Arena (MOBA), seperti Mobile Legends dianggap menuntut para pemainnya untuk memberikan atensi lebih ketika bermain misalnya dalam menyusun strategi yang efektif untuk bisa memenangkan permainan. Penelitian ini bertujuan untuk mengetahui perbedaan atensi pada gamers dan non gamers. Penelitian ini menggunakan metode eksperimen dengan desain penelitian between-subject serta melibatkan 60 partisipan yang terdiri dari 30 gamers MOBA sebagai kelompok kontrol dan 30 non-gamers MOBA sebagai kelompok eksperimen. Adapun atensi partisipan diukur menggunakan alat ukur tingkat atensi pada aplikasi CogLab versi 2.0. Hasil penelitian yang dilakukan melalui uji independent samples t-test menunjukkan bahwa terdapat perbedaan yang signifikan atas atensi pada gamers dan non gamers dengan nilai signifikansi p = 0.039. sehingga kesimpulannya adalah tingkat atensi pada partisipan gamers sebagai kelompok kontrol menunjukkan hasil yang lebih tinggi dibanding partisipan non gamers sebagai kelompok eksperimen.